The clover-like deformity of gallbladder: A case report - KOIDE, Shigeki; KIKUYAMA, Masataka; OOTA, Yuji; HIRAI, Ritsuko; SASADA, Yuzou (Tando, 2006)
A 64-year-old man was admitted for evaluation of the gallbladder wall thickness, pointed out with ultrasonographic examination during follow-up due to post operation state of sigmoid colon cancer. ERCP revealed the clover-like deformity with poolings of contrast medium in the wall of the gallbladder. Macroscopic observation of the resected specimen showed the ulcer scars and the wall thickness of the gallbladder fundus. Histopathologically, the lesions were formed with fibrosis extended to the subserosal layer accompanied with endothelium hypertrophy and thrombosis of the cystic artery around the lesions, and Rokitansky-Aschoff sinus hypertrophy with wall thickness of the gallbladder. We consider the lesions of the gallbladder fundus were healed ulcers formed with ischemia due to the thrombosis with endothelium hypertrophy. This case suggests the pathogenesis of spontaneous gallbladder perforations.